TINJAUAN SOSIOLOGI HUKUM TERHADAP KESADARAN HUKUM MASYARAKAT DALAM MENGGUNAKAN SURAT IZIN MENGEMUDI (SIM) DI WILAYAH HUKUM POLRES BUTON - La Ode Bunga Ali; La Ode Asrim; Nurdin Nurdin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2023)
This study aims 1. To determine the level of public legal awareness in owning or using a driving license in Buton District. 2. To find out the obstacles and countermeasures faced by the Police in handling public legal awareness of using a SIM in traffic in Buton Regency. The method used in this study was empirical legal research by collecting data through document studies, interviews, and questionnaires for respondents. Sampling was carried out non-randomly with a purposive sampling technique. Data were analyzed using qualitative analysis The results of the study show that the level of public legal awareness in traffic is very low, even though law enforcement against motor vehicle violations in the jurisdiction of the Buton Police has been carried out routinely. The obstacle faced by the police in handling public legal awareness in traffic is that the community lacks and does not understand, and even ignores traffic rules.